A 3 year retrospective study of pregnancies complicated with placenta previa in a tertiary care centre - Kamath, Vatsala; Aravind, Aparna C.; Shettian, Nishita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Placenta previa describes when a placenta is implanted partially or completely over the internal OS. About one third of the ante partum haemorrhage belongs to placenta previa. The incidence is increased beyond the age of 35 years, with high birth order pregnancies, prior caesarean deliveries and in multiple pregnancy. The aim of the study was to determine maternal and fetal outcome in pregnancies complicated with placenta previa. Methods: A 3 year retrospective study done in OBG department of A. J. Institute of Medical Sciences, Mangalore from January 2017- January 2020. All pregnant women who are diagnosed with placenta previa during regular antenatal care (ANC) follow up, at or after admission and during caesarean delivery are included in the study. Data were collected from the hospital records. Results: During the study period, there were 34 pregnant women with placenta previa. Maximum were in the age group of 31-35 years of age and 8.82 percentage were in the age group more than 35 years. Out of the study subjects,76.5 percentage were multigravidas and 50 percentage were giving history of prior one caesarean section. 29.4 percentage of study subjects had true placenta previa and 85.2 percentage underwent elective caesarean section. There were significantly higher number of babies required neonatal intensive care unit (NICU) admissions. Conclusions: An increase in the incidence of women with advanced maternal age, multiparity, prior caesarean deliveries contributes to a rise in the number of pregnancies complicated with placenta previa.